Theoretical and experimental analysis of a salt gradient solar pond with insulated and reflective covers - Bezir, Nalan Cicek; Ozek, Nuri; Kayal, R.; Yakut, Ali Kemal; Sencan, Arzu; Kalogirou, Soteris A. (My University, 2009)
In this study, a salt gradient solar pond having a surface area of 3.5 × 3.5 m2 and depth of 2 m has been built for supplying hot water to a leather workshop on the campus area of Vocational College of Isparta/Yalvaç. A cover system was used on the surface of the pond to reduce the thermal losses from the top to air and to increase the thermal efficiency of the pond. Such an arrangement is used for the very first time. The system is composed of two covers that can be rotated between 0 and 180 degrees by a controlled electric motor and has insulation and reflection properties, i.e., the covers function as insulators when closed and as reflectors when opened. The pond's thermal analysis has been carried out theoretically and experimentally for different operating conditions. Results obtained from this study show that salt gradient solar ponds can be used as a source of warm water required at the leather workshop and for suitable domestic applications. The covers were effective both for reducing the night thermal losses and for increasing the daytime performance, although the former effect is negligible
Keywords: Solar ponds; Thermal analysis; Electric machinery; Lakes; Leather